Indonesian to English Noun Phrase Meaning Equivalence on Food Lists from Several Restaurants in Ubud Gianyar Bali - Hartanti Woro Susianti; Ni Wayan Pastini (LACULTOUR: Journal of Language and Cultural Tourism, 2022)
The declining number of arrival of foreign tourists to the island of Bali has led to some intense competition in obtaining customers in restaurants, located in the area of Ubud Gianyar. To anticipate such things, foreign language skill, especially English is very important, especially for waiters in restaurants, who are required to be able to explain the food/menu in English, so the customers will feel satisfied because they understand the food ordered. This study aims to describe the equivalence of Indonesian phrases in English about food on the food lists in several restaurants in Ubud. The data were analyzed using qualitative linguistic theory, which relies on a phenomenological philosophical approach. The results showed that all restaurants used Modificative Noun phrases, and 80% of them also used Appositive noun phrases.  While Coordinative Noun phrases are only used by 10% of restaurants. Furthermore, it is suggested to the restaurant managers to use simpler noun phrases, so that it becomes easier for guests to understand the meaning of Indonesian phrases that are stated in English noun phrases. In addition, it will also make it easier for waiters to explain the food menu available at the restaurant.   Keywords: noun phrase, renu, Restaurant